KUALITAS HIDUP ANAK PENDERITA TALASEMIA DI RSUD KRT SETJONEGORO WONOSOBO BERDASARKAN INSTRUMEN PEDIATRIC QUALITY OF LIFE INVENTORY 4.0 GENERIC CORE SCALES (PedsQL) - Purnamasari, Ika; Supriyati, Amanah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Purpose: This study aims to describe the quality of life of children with thalassemia based on the Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL) instrument Methods: This research is an analytical descriptive study with a cross sectional approach. The sample numbered 23, which was a total sampling of pediatric patients aged 2 to 18 years who were routinely undergoing thalassemia treatment at Wonosobo Regional Hospital. Data was collected using the Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL) instrument. Data analysis uses descriptive analysis and based on the PedsQL instrument scoring with data from children's reports. Results: Most of the children with thalassemia had a good quality of life with an average score of 88.32, 82.6% and the remainder had a poor quality of life, 17.4% with an average score of 64.67. School function is the quality of life domain with the lowest score and social function with the highest score. Conclusion: Most children suffering from thalassemia at KRT Setjonegoro Wonosobo Regional Hospital have a good quality of life. This condition has the potential to increase children's productivity and happiness.